Mismatch between urban eco-sanitation improvement and health service supply capacity: evidence from Chinese city panel data and interpretable machine learning - Zhen Peng; Lin Wang (BMC Health Services Research, 2026)
Abstract Background Health service supply capacity depends not only on medical resource stocks but also on urban eco-sanitation conditions and resource-allocation mechanisms. Existing studies focus mainly on environmental exposure and health outcomes, with limited attention to whether eco-sanitation improvements can be converted into health service supply capacity. Methods This study constructed a panel of Chinese prefecture-level and above cities for 2002–2024, using the health service supply capacity index as the dependent variable and the eco-sanitation environment index as the core explanatory variable. Two-way fixed effects models, dimension-specific analysis, mechanism tests, heterogeneity analysis, robustness checks, and interpretable machine learning identified mismatch mechanisms and boundary conditions. The mechanism analysis was extended to two- and three-year ESE lags and one- and two-year lagged investment variables. Carbon-emission comparability was reassessed on exact CEADs-matched samples for 2002–2019. Hu Huanyong line subgroup models were additionally estimated with city and province-year fixed effects. Results The eco-sanitation environment, green infrastructure, and municipal sanitation facilities improved continuously, whereas health service supply capacity increased more slowly. The baseline model does not support a stable positive conversion from eco-sanitation improvement to stronger supply capacity. Dimension-specific results reveal differentiated roles. The positive PPI coefficient must not be read as a pollution benefit; it is consistent with a demand-induced or compensatory resource-allocation response. Neither two- to three-year ESE lags nor one- to two-year lagged investment variables produced a stable urban construction investment transmission chain. The positive CEADs interaction was confirmed only within the 2002–2019 matched sample and therefore represents pre-pandemic evidence. The southeastern Hu-line coefficient attenuated and lost conventional significance after province-year policy shocks were absorbed. Machine learning indicates the relationship is shaped by development stage, population size, fiscal capacity, and nonlinear boundaries. Conclusions Eco-sanitation improvement is not a sufficient condition for enhancing health service supply capacity. Healthy city development should integrate eco-sanitation governance, infrastructure investment, workforce allocation, and fiscal arrangements into a unified governance framework. Because HSC is a supply-side proxy based on resource counts, these implications concern resource availability and network density rather than quality of care, realized utilization, accessibility, or overall health-system performance.